The Ebola Threat: China's Response to the West African Epidemic and National Development of Prevention and Control Policies and Infrastructure. (7th January 2015) - Fan, Hao-Jun; Gao, Hong-Wei; Ding, Hui; Zhang, Bi-Ke; Hou, Shi-Ke
Abstract: There is growing concern in West Africa about the spread of the Ebola hemorrhagic fever virus. With the increasing global public health risk, a coordinated international response is necessary. The Chinese government is prepared to work in collaboration with West African countries to assist in the containment and control of the epidemic through the contribution of medical expertise and mobile laboratory testing teams. Nationally, China is implementing prevention programs in major cities and provinces, the distribution of Ebola test kits, and the deployment of a new national Ebola research laboratory. ( Disaster Med Public Health Preparedness . 2015;0:1-2)